Paradoks Hukum Keadaan Darurat dalam Pasal 12 UUD 1945: Menghindari State of Exception yang Permanen dalam Sistem Hukum Tata Negara Indonesia - Sudirman Sudirman; Fathul Hamdani; Arifuddin Uksan; Parluhutan Sagala; Irwan Triadi (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2026)
This article explores the inherent constitutional tensions within Article 12 of the 1945 Constitution of the Republic of Indonesia, which grants the President the authority to declare a state of danger. The primary problem identified in this study centers on the operational paradox of Article 12 through an outdated regulation, namely Law Number 23 of 1959 concerning the State of Danger. The crucial issues of this regulation include the granting of a 'blank check' (blanco mandaat) to the President without clear time limits, the absence of legislative (DPR) and judicial oversight, and its excessively militaristic nature, which renders it incapable of responding to modern crises such as health pandemics or cyber-attacks. Utilizing the analytical framework of the intellectual debate between Carl Schmitt and Hans Kelsen, this research dissects whether Indonesia currently leans toward an absolute decisionist sovereignty model or a controlled normativism model. A crucial issue is identified in the existence of Law Number 23 of 1959 concerning the State of Danger, which is deemed outdated, militaristic, and lacking in oversight, thereby potentially creating